PERLU DIAGNOSIS KESULITAN BELAJAR DALAM PEMBELAJARAN IPA DAN HUBUNGANNYA DENGAN PENGAJARAN REMIDIAL - Waruwu, Henoki (IKIP Gunungsitoli, 2009)
Abstrak: Many students Â have difficulty in learning generaly. Therefore requireÂ to be diagnosed especially in learning difficulty of IPA. As follow-up must conducted] by instruction of remedial.Key words: learning difficulty, instruction of remidial